Evaluation of combinatorial cis-regulatory elements for stable gene expression in chicken cells - Seo Hee W (BMC Biotechnology, 2010)
Abstract Background Recent successes in biotechnological application of birds are based on their unique physiological traits such as unlimited manipulability onto developing embryos and simple protein constituents of the eggs. However it is not likely that target protein is produced as kinetically expected because various factors affect target gene expression. Although there have been various attempts to minimize the silencing of transgenes, a generalized study that uses multiple cis-acting elements in chicken has not been made. The aim of the present study was to analyze whether various cis-acting elements can help to sustain transgene expression in chicken fibroblasts. Results We investigated the optimal transcriptional regulatory elements for enhancing stable transgene expression in chicken cells. We generated eight constructs that encode enhanced green fluorescent protein (eGFP) driven by either CMV or CAG promoters (including the control), containing three types of key regulatory elements: a chicken lysozyme matrix attachment region (cMAR), 5'-DNase I-hypersensitive sites 4 (cHS4), and the woodchuck hepatitis virus posttranscriptional regulatory element (WPRE). Then we transformed immortalized chicken embryonic fibroblasts with these constructs by electroporation, and after cells were expanded under G418 selection, analyzed mRNA levels and mean fluorescence intensity (MFI) by quantitative real-time PCR and flow cytometry, respectively. We found that the copy number of each construct significantly decreased as the size of the construct increased (R2 = 0.701). A significant model effect was found in the expression level among various constructs in both mRNA and protein (P < 0.0001). Transcription with the CAG promoter was 1.6-fold higher than the CMV promoter (P = 0.027) and the level of eGFP expression activity in cMAR- or cHS4-flanked constructs increased by two- to three-fold compared to the control CMV or CAG promoter constructs. In addition, flow cytometry analysis showed that constructs having cis-acting elements decreased the level of gene silencing as well as the coefficient of variance of eGFP-expressing cells (P < 0.0001). Conclusions Our current data show that an optimal combination of cis-acting elements and promoters/enhancers for sustaining gene expression in chicken cells is suggested. These results provide important information for avian transgenesis and gene function studies in poultry.